SIC and PIC multiuser detection for prefix-assisted DS-CDMA systems - Silva, Paulo (2009)
In this paper we present iterative frequency-domain multiuser detection (MUD) receivers for the uplink transmission of direct sequence code division multiple access systems (DS-CDMA) that combine iterative block decision feedback equalization (IB-DFE) principles with interference cancelation techniques. Both successive interference cancelation (SIC) and parallel interference cancelation (PIC) structures are considered. Our performance results show that the proposed receiver structures have excellent bit error rate (BER) performances, that can be close to the single-user matched filter bound (MFB), even for fully loaded systems and severely time-dispersive channels1.